Lessons for LEED® for Neighborhood Development, Social Equity, and Affordable Housing. Issue 1 (2nd January 2016) - Szibbo, Nicola
Abstract : Problem, research strategy, and findings: Leadership in Energy and Environmental Design® for Neighborhood Development (LEED®ND) is a rating system designed to encourage sustainable development. I explore why and how most LEED®ND projects ultimately fail to meet the equity goals inherent in sustainability. I survey 114 LEED®ND accredited professionals (APs) and conduct 20 interviews with LEED®ND APs to illuminate the role of the rating system in developer decisions to include affordable housing in their projects. I also explore why nonprofit developers see value in seeking LEED®ND certification for their projects. Although a limited sample, it provides insights into how the certification process affects developer decisions. I find that the LEED®ND rating system does a poor job of encouraging developers to provide affordable housing: Only 40% of LEED®ND-certified projects include affordable housing. LEED®ND APs do not feel that the system offers sufficient incentives to overcome the risks and costs of providing affordable housing. Nonprofit developers might pursue LEED®ND to create savings for residents, but may be deterred by the cost of certification. Most respondents feel that the affordable housing credit should be increased and improved to provide adequate incentives to developers. Takeaway for practice: Planners cannot count on LEED®ND certification to ensure the provision of affordable and mixed housing in sustainable neighborhoods. The LEED®ND system could be improved by weighting the affordable housing credit more heavily; developers could also be incentivized to build a greater mix of housing. The certification costs could be lowered or subsidized for projects with affordable housing and assessed on a per unit basis. Additional credits could be given to projects that significantly reduce utility costs for low-income residents.